The Influence Of Attitudes Toward Brands And Attitudes Toward Advertising On Brand Preferences On Advertisements For Dove Shampoo Products (Case Study On Consumers Of Dove Shampoo Products At Minimarket X In Tasikmalaya City) - Cita Sindy Lestari; Rizki Zulfikar (Fakultas Ekonomi dan Bisnis Universitas Komputer Indonesia, 2022)
This study was conducted to determine the respondents' assumptions about attitudes to brands, assumptions about attitudes to advertising and respondents' assumptions about brand preferences, as well as how much attitudes to brands and attitudes to advertising affect brand preferences either simultaneously or partially. The research method in this study used descriptive and verification methods and quantitative approaches, the number of samples used in this study was 100 respondents. The methods used include Multiple Linear Regression Test, Classical Assumption Test, Correlation and Hypothesis Testing and using SPSS v21.1 software tools. The results showed that consumers of dove shampoo products at Mimimarket X in the City of Tasikmalaya already had a fairly good brand attitude, consumers of Dove shampoo products at Mimimarket X in Tasikmalaya City already had a fairly good advertising attitude, consumer products of Dove shampoo at Mimimarket X in the City of Tasikmalaya. Tasikmalaya already has a fairly good brand preference. So that the variables of Attitude on the brand and Attitude on advertising together have a significant influence on brand preference.